SYSTEM APPROACH TO THE ORGANIZATION OF SCIENTIFIC WORK STUDENTS IN HIGHER SCHOOL CONDITIONS (Pedagogy of Higher and Secondary Education, 2003)
The article deals with the systematic approach to the organization of students self-government and scientific work.